METHODS OF MORAL EDUCATION OF CHILDREN IN PRE-SCHOOL EDUCATIONAL ORGANIZATIONS (International journal of artificial intelligence, 2025)
provides information for educators in moral education of children in preschool educational organizations and explains methods of organization in each group. Annotation provides information for educators in moral education of children in preschool educational organizations and explains methods of organization in each group.